Conductive framework supported high rate performance of SnO2 hollow nanofibers for lithium battery anodes. (10th April 2015) - Pham-Cong, De; Kim, Ji Yoon; Park, Jung Soo; Kim, Jae Hyun; Kim, Jong-Pil; Jeong, Euh-Duck; Kim, Jinwoo; Jeong, Se-Young; Cho, Chae-Ryong
Graphical abstract: Abstract: We synthesized an electrospun SnO2 hollow nanofibers (SnO2 hNFs) coated with carbon and wrapped with graphene oxide layer by simple hydrothermal and electrostatic force method, respectively. Thin carbon layer as electrolyte blocking layer was formed on the SnO2 hNFs by using glucose as a carbon source (SnO2 @C hNFs). Also, layers of graphene oxide are wrapped on SnO2 @C hNFs by the electrostatic interaction force (SnO2 @C@G hNFs). At high C rate, the average capacity of the SnO2 @C@G hNFs still kept high capacity comparing with the SnO2 hNFs and SnO2 @C hNFs and then increased above 250% at 3 C. It also exhibits a greatly enhanced synergic effect with an extremely high lithium storage capability up to 1, 600 mA h g −1 and kept 900 mA h g −1 after 50 cycles benefiting from the advanced structural features.